Graphene synthesis, fabrication, characterization based on bottom-up and top-down approaches: An overview. (1st June 2022) - Olatomiwa, Agbolade Lukman; Adam, Tijjani; Gopinath, Subash C. B.; Kolawole, Sanusi Yekinni; Olayinka, Oyeshola Hakeem; Hashim, U.
Abstract: This study presents an overview on graphene synthesis, fabrication and different characterization techniques utilized in the production. Since its discovery in 2004 by Andre Geim and Kostya Novoselov several research articles have been published globally to this effect, owing to graphene's extraordinary, and exclusive characteristics which include optical transparency, excellent thermal, and mechanical properties. The properties and applications of this two-dimensional carbon crystal composed of single-layered material have created new avenues for the development of high-performance future electronics and technologies in energy storage and conversion for the sustainable energy. However, despite its potential and current status globally the difficulty in the production of monolayer graphene sheet still persists. Therefore, this review highlighted two approaches in the synthesis of graphene, which are the top-down and bottom-up approaches and examined the advantages and failings of the methods involved. In addition, the prospects and failings of these methods are investigated, as they are essential in optimizing the production method of graphene vital for expanding the yield, and producing high-quality graphene.